Healthy people, soils, and ecosystems: uncovering primary drivers in the adoption of regenerative agriculture by US farmers and ranchers - Frankel-Goldwater, Lee; Wojtynia, Niko; Dueñas-Ocampo, Sebastián (Frontiers in Sustainable Food Systems, 2024)
As regenerative agriculture grows in popularity, policy and decision-makers have become interested in its practices. Yet, little is known about those factors driving its adoption among farmers and ranchers. To better understand these drivers, we conducted semi-structured interviews with 31 farmers and ranchers across the United States (US) who self-identified as practitioners of regenerative agriculture. In doing so, we asked about relational values, which reflect one’s perspectives around the links between humans and nature. We also asked about economic and environmental drivers for adoption. In the analysis, we used qualitative coding to identify the range of values and factors driving adoption across our sample. We found that 1) improving the health of people, soils, and ecosystems - through farming practices and related social configurations - was a primary driver for adoption, 2) that relative economic privilege, particularly across two extremes - privileged idealism and less privileged necessity - correlated with most drivers for adoption, 3) that a shift away from industrial agriculture was at once a moral, economic, and environmental imperative for many practitioners, and 4) a systems view of social-ecological relationships was seen as a key to adoption and societal transitions. While our sample represents only a narrow segment of the regenerative agriculture movement in the US, our findings can serve as a useful starting point for understanding the drivers for its adoption. Our findings may also inform conversations on regenerative agriculture’s potential to support food-related sustainability transitions. The discussion situates our work amidst sustainable agriculture and social movement studies, questions of equity in food systems transitions, and the benefits of studying values in developing policy-relevant solutions.